Changeable and Reconfigurable Manufacturing Systems - ElMaraghy, Hoda A. (Springer Series in Advanced Manufacturing, 2009)
Change, in products and systems, has become a constant in manufacturing. Changeable and Reconfigurable Manufacturing Systems discusses many key strategies for success in this environment. Changes can most often be anticipated but some go beyond the design range. This requires providing innovative change enablers and adaptation mechanisms. Changeable and Reconfigurable Manufacturing Systems presents the new concept of changeability as an umbrella framework that encompasses many paradigms such as agility, adaptability, flexibility and reconfigurability. The book provides the definitions and classification of key terms in this new field, and emphasizes the required physical/hard and logical/soft change enablers. Over 22 chapters, the book presents cutting edge technologies, the latest thinking and research results, as well as future directions to help manufacturers stay competitive. It contains original contributions and results from senior international experts, experienced practitioners and accomplished researchers in the field of manufacturing, together with industrial applications. Changeable and Reconfigurable Manufacturing Systems serves as a comprehensive reference and textbook for industrial professionals, managers, engineers, specialists, researchers and academics in manufacturing, industrial and mechanical engineering; and general readers who are interested to learn about the new and emerging manufacturing paradigms and their potential impact on the workplace and future jobs.